ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DENGAN BANK KONVENSIONAL DI INDONESIA - Argarina, Argarina; Kamaliah, Kamaliah (Jurnal Tepak Manajemen Bisnis, 2016)
This research is performed in order to compare the financial performance ofIslamic Banks with Conventional Banks, with the variables studied are ROA (Return onAssets), DER (Debt Equity Ratio), BOPO (Operating Expense to Operating Income), NPL(Net Performing Loan), LDR ( Loan To Deposit Ratio) and CAR (Capital AdequacyRatio).The population is all of Islamic Banks and Conventional Banks in Indonesia. Thedata is based on the publication of banking directory Indonesia since 2010 until 2014.Obtained by amount sampel as much 11 Islamic Banks and 107 Conventional Bank inIndonesia 2010-2014 period. The analytical method used is the Non Parametric Analysisof Two Related Samples Test namely the Kolmogorov-Smirnov test.Based on data analysisfound that there was significant difference from the average value of ROA, DER, BOPO,NPL and LDR, between Islamic Banks and Conventional Banks. As for the CAR ratio thereare no significant differences. Overall the study period performance of Islamic Bank betterthan Conventional Banks though seen from an average of all ratios Conventional Banknicer. Islamic Bank better but according to the author analyzes because during themonetary crisis can still survive and when the economy is not conducive Islamic Bank NPLincrease but still below the Bank Conventional NPL.